2020
DOI: 10.1002/aelm.202000940
|View full text |Cite
|
Sign up to set email alerts
|

Optically Controlled Ternary Logic Circuits Based on Organic Antiambipolar Transistors

Abstract: A ternary inverter is demonstrated based on an organic antiambipolar transistor (AAT), in which the output logic states can be precisely controlled with appropriate optical signals. First, the photoresponse of AATs consisting of PTCDI‐C8 and α‐6T layers is systematically investigated. Under visible light, the Λ‐shaped transfer curve of the AATs undergoes a noticeable broadening due to the optically induced threshold voltage shift in both the PTCDI‐C8 and α‐6T controlled ranges. Under ultraviolet light, broaden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 37 publications
(49 reference statements)
0
33
0
Order By: Relevance
“…Due to this attractive feature, multivalued logic circuits (MVLs), such as ternary and quaternary inverters, have recently been realized, and their development is another significant strategy for improving the data processing capability of the currently used logic circuits. [39][40][41][42][43][44][45] In contrast to the abovementioned efforts on MVLs, our approach is to apply AATs to electrically reconfigurable logic circuits. A dual-gate configuration enables the control of the used Λ-shaped drain current by three input signals: bottom-gate, top-gate, and drain voltages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to this attractive feature, multivalued logic circuits (MVLs), such as ternary and quaternary inverters, have recently been realized, and their development is another significant strategy for improving the data processing capability of the currently used logic circuits. [39][40][41][42][43][44][45] In contrast to the abovementioned efforts on MVLs, our approach is to apply AATs to electrically reconfigurable logic circuits. A dual-gate configuration enables the control of the used Λ-shaped drain current by three input signals: bottom-gate, top-gate, and drain voltages.…”
Section: Introductionmentioning
confidence: 99%
“…Due to this attractive feature, multivalued logic circuits (MVLs), such as ternary and quaternary inverters, have recently been realized, and their development is another significant strategy for improving the data processing capability of the currently used logic circuits. [ 39–45 ]…”
Section: Introductionmentioning
confidence: 99%
“…Based on the AAT devices, Panigrahi et al observe that the logic state levels and their ratio can be controlled under light irradiation. 85 Since the capability of photoresponse are different for the two semiconductors, to be specific, the threshold voltage shift and the current enhancement of the p-type α-6 T are larger than that of the n-type PTCDI-C8, the change in antiambipolar transfer characteristics of the AAT under UV and visible light mainly occurs in the α-6 T controlled range. Taking advantage of the optically tunable antiambipolar characteristics, an optically controlled ternary inverter is fabricated.…”
Section: Organic Digital Circuitsmentioning
confidence: 99%
“…The integrated inverter produces the third state of "1/2" excluding "1" and "0" at the voltage transport curve, which is called a ternary inverter. Study of the ternary inverter is highly meaningful because of the high density of the data and simplification of the circuit system [112], and there were attempts to implement a hybrid ternary inverter. In 2020, Park et al reported a photo-triggered ternary inverter using a rubrene nanosheet (NS) TFT and a rubrene/MoS 2 n-p heterojunction antiambipolar transistor (AAT) (Figure 6a,b) [113].…”
Section: Multivalued Logicsmentioning
confidence: 99%